Immune-Mediated Platelet Activation in COVID-19 and Vaccine-Induced Immune Thrombotic Thrombocytopenia - Uzun, Günalp; Pelzl, Lisann; Singh, Anurag; Bakchoul, Tamam (Frontiers in Immunology, 2022)
Both qualitative and quantitative platelet abnormalities are common in patients with coronavirus disease 2019 (COVID-19) and they are correlate with clinical severity and mortality. Activated platelets contribute to the prothrombotic state in COVID-19 patients. Several groups have shown immune-mediated activation of platelets in critically ill COVID-19 patients. Vaccine-induced immune thrombotic thrombocytopenia is an autoimmune condition characterized by thrombocytopenia and life-threatening thrombotic events in the arterial and venous circulation. Although the initial trigger has yet to be determined, activation of platelets by immune complexes through Fc gamma RIIA results in platelet consumption and thrombosis. A better understanding of platelet activation in COVID-19 as well as in vaccine-induced thrombotic complications will have therapeutic implications. In this review, we focused on the role of immune-mediated platelet activation in thrombotic complications during COVID-19 infection and vaccine-induced immune thrombotic thrombocytopenia.